2016
DOI: 10.1245/s10434-016-5306-0
|View full text |Cite
|
Sign up to set email alerts
|

CRS-HIPEC Prolongs Survival but is Not Curative for Patients with Peritoneal Carcinomatosis of Gastric Cancer

Abstract: We provide retrospective evidence that multimodal treatment with gastrectomy, CRS, and HIPEC is associated with improved survival for patients with PC of advanced gastric cancer compared with gastrectomy and palliative chemotherapy alone. We also show that patients treated with CRS-HIPEC have comparable survival to matched control patients without PC. However, regardless of treatment scheme, all patients subsequently recur and die of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 14 publications
1
34
0
5
Order By: Relevance
“…On the contrary the diagnosis of PC in addition to any stage of GC has been traditionally considered a cut off point for surgical intervention and has always been treated with palliative chemotherapy. This creates a situation where locally advanced cancers with positive lymph nodes are subject to aggressive multimodality treatment, whereas less advanced tumors with PC, which can be considered a result of loco regional extension of the primary cancer into the peritoneal cavity, are treated with palliative chemotherapy (3). Without any doubt PC caused by GC represents a poor long-term survival clinical situation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary the diagnosis of PC in addition to any stage of GC has been traditionally considered a cut off point for surgical intervention and has always been treated with palliative chemotherapy. This creates a situation where locally advanced cancers with positive lymph nodes are subject to aggressive multimodality treatment, whereas less advanced tumors with PC, which can be considered a result of loco regional extension of the primary cancer into the peritoneal cavity, are treated with palliative chemotherapy (3). Without any doubt PC caused by GC represents a poor long-term survival clinical situation.…”
Section: Introductionmentioning
confidence: 99%
“…However, advanced GC with advanced lymphatic spread has a comparable prognosis. The difference between these two above mentioned scenarios is that PC can be diagnosed early with a staging laparoscopy, while lymphatic spread is usually a postoperative pathological diagnosis (3). Moreover these patients more frequently die for peritoneal spread of the disease than for distant metastases (77% of patients without distant metastasis die due to peritoneal progression of disease) despite a radical surgery and radiochemotherapy regimes (4).…”
Section: Introductionmentioning
confidence: 99%
“…Results showed increased 1-, 2-, and 3-year mortality rates, decreased rates of peritoneal recurrence, and decreased rates of hematogenous metastasis in the group analogous to CRS-HIPEC. 13 Likewise, Boerner et al 14 showed that the combination of HIPEC with CRS doubled patients' 2-year survival rates (35.8% vs 16.9%) compared with traditional chemotherapy with gastrectomy. Impressively, this study showed that patients treated with CRS-HIPEC have comparable survival to matched patients who do not have peritoneal metastases.…”
Section: The Effect Of Hipec On Gastric Cancer Mortalitymentioning
confidence: 99%
“…Although, there have been rapid progresses in research and clinical care in GC during the past few years, patients with GC and peritoneal carcinomatosis (PC) have limited intervention options due to poor response to systemic chemotherapy, and the survival rate is extremely low. Once GC spread to the peritoneum, the 5-year survival is expected to be less than 5% (2). C y t o r e d u c t i v e s u r g e r y ( C R S ) c o m b i n e d w i t h hyperthermic intraperitoneal chemotherapy (HIPEC) has been shown to dramatically improve survival in patients with PC from colorectal cancer, and similar findings have also been reported in patients with advanced GC with PC (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Once GC spread to the peritoneum, the 5-year survival is expected to be less than 5% (2). C y t o r e d u c t i v e s u r g e r y ( C R S ) c o m b i n e d w i t h hyperthermic intraperitoneal chemotherapy (HIPEC) has been shown to dramatically improve survival in patients with PC from colorectal cancer, and similar findings have also been reported in patients with advanced GC with PC (2,3). In a recent report, in patients with adjuvant HIPEC performed with R0 gastric surgery, the 3-and 5-year overall survival rate was 94.0% and 86.8% in patients with…”
Section: Introductionmentioning
confidence: 99%